Intangible activities—the prevalence of informal helping in Denmark. Issue 4 (1st October 2016) - Hermansen, Jonathan
ABSTRACT: 'Informal helping' is often associated with other types of prosocial behaviour such as formal voluntary work. Therefore, one could jump to the conclusion that it would be the same factors driving both types of activities. This article demonstrates that this is not the case. The study relies on a population survey on informal helping and volunteering in Denmark. The two contributions of this article are as follows: (1) it demonstrates that the socio-demographic indicators that are closely linked to formal volunteering are not related to informal helping in the same manner and (2) it demonstrates that it is necessary to separate the decision to help and the amount of hours that people help, a distinction that previous empirical studies on this topic fail to include. The results show that informal helping may not simply be compared to other instances of prosocial behaviour. In particular, the socio-demographic indicators that are closely linked to formal volunteering are not necessarily related to informal helping. Moreover, the results emphasize the need for including informal helping as an act of civic engagement, which ought not to be confused with other forms of engagement within the civil society.